Respostas

2014-05-10T00:46:39-03:00
A)10y-5-5y=6y-6-20
5y-6y=-26+5
-y=-21(-1)
y=21

b)x²+4x+x²+2x=4x+12
2x²+2x=12
x1=0
2x+2=12
2x=10
x=10/2
x2=5

c)4x²+24-x²=10x²
3x²-10x²=-24
-7x²=-24(-1)
7x²=24
x²=24/7
x=√3,42
x=1,85
4 4 4
2014-05-10T00:59:10-03:00
A) 10y-5(1+y) =3 (2y-2) -20
10y-5-5y=6y-6-20
10y-5y-6y=--6-20+5
-y=-21.(-1)
y=21

B) x(x+4) +x(x+2)= 2x² + 12
x²+4x+x²+2x=2x²+12
2x²+6x-2x²=12
6x=12
x=12/6
x=2

C) 4x(x+6) -x² = 5x²
4x²+24x-x²=5x²
4x²-x²-5x²-24x=0
-2x²-24x=0

x(-2x-12)=0
x¹=0

-2x-12=0
-2x=12
x=12/-2
x²=-6
4 4 4